Acute effect of isometric wall squat on hemodynamic and autonomic status according to sex in patients with hypertension (2025)
Objective Isometric wall squat training (IWST) is one of the most effective exercise modalities for lowering blood pressure. Among the physiological mechanisms contributing to this effect, the reduction in total peripheral resistance (TPR) is particularly relevant. There are differences in pathophysiology between men and women in hypertension (HTN); it is unknown whether the effect of IWST is heterogeneous according to sex. This study aims to evaluate the acute hemodynamic and autonomic responses to IWST according to sex in patients with newly diagnosed HTN. Methods Quasi-experimental study that included patients with recently diagnosed HTN in whom the hemodynamic and autonomic response during a IWST session (4-repetition) was evaluated using impedance cardiography according to sex. The diagnosis of high blood pressure was confirmed by 24-hour ambulatory blood pressure monitoring. Results Among the patients included (n=74), the average age was 53.0  6.8 years; 56.7% (n=42) were men. Women showed a smaller increase in heart rate (HR) (–5.1; 95% CI: –9.3 to –0.8 bpm; p value = 0.019), and total peripheral resistance index (TPRI) (–299.6; 95% CI: –487.1 to –112.1 dyne·s·m²/cm⁵; p value = 0.002), less reduction in stroke volume index (SVI) (3.1; 95% CI: 0.8 to 5.4 mL/m2; p value = 0.009), and a greater increase in cardiac index (CI) (0.3; 95% CI: 0.03 to 0.5 L/min·m2; p value = 0.025) compared to men during the isometric squat repetitions. Likewise, during the recovery periods, women showed a greater reduction in HR (–6.0; 95% CI: –9.5 to –2.4 bpm; p value = 0.001) and TPRI (–181.0; 95% CI: –357.5 to –4.4 dyne·s·m²/cm⁵; p value = 0.045), a greater increase in SVI (3.0; 95% CI: 1.0 to 5.0 mL/m2; p value = 0.004), greater reduction in the sympathetic activity (LF/HF ratio) (–1.1; 95% CI: –2.2 to –0.05; p value = 0.041) and greater increase in spontaneous baroreflex sensitivity (SBS) (2.4; 95% CI: 0.5 to 4.2 ms/mmHg; p value = 0.011) compared to men. Notably, women showed a smaller increase in HR (–7.9; 95% CI: –12.4 to –3.3 bpm; p value = 0.001) following IWST, with no other between-sex differences observed post-session. Conclusion Individuals with newly diagnosed arterial HTN without anti-hypertensive pharmacological treatment present a heterogeneous hemodynamic and autonomic response during an IWST session according to sex. Women exhibit a smaller increase in TPR, greater increase in CI during the isometric squat, and greater reductions in TPR during recovery periods, accompanied by a better autonomic control, compared to men. These findings highlight the potential value of considering sex-specific mechanisms when prescribing isometric training as a non-pharmacological intervention for blood pressure control. Further studies are needed to evaluate chronic adaptations to this training modality.